Copying the master and stealing his secrets : talent and training in Japanese painting - Jordan, Brenda G.; Weston, Victoria Louise (University of Hawaiʻi Press, 2003)
Focus is on pedagogical approaches used by masters who were trained by Kano or Kano lineage painters during the 17th through 19th centuries. This volume is illustrated with reproductions of Japanese artwork in b & w and color.